The effects of virtual reality game training on trunk to pelvis coupling in a child with cerebral palsy - Barton, Gabor J (BioMed Central, 2013)
BACKGROUND: Good control of trunk and pelvic movements is necessary for well controlled leg movements required to perform activities of daily living. The nature of movement coupling between the trunk and pelvis varies and depends on the type of activity. Children with cerebral palsy often have reduced ability to modulate coupling between the trunk and pelvis but movement patterns of the pelvis can be improved by training. The aim of this study was to examine how pelvis to trunk coupling changed while playing a computer game driven by pelvic rotations. METHODS: One boy with cerebral palsy diplegia played the Goblin Post Office game on the CAREN virtual rehabilitation system for six weeks. He navigated a flying dragon in a virtual cave towards randomly appearing targets by rotating the pelvis around a vertical axis. Motion of the pelvis and trunk was captured in real-time by a Vicon 612 optoelectronic system tracking two clusters of three markers attached to the sacrum and thoracic spine. RESULTS: Convex hull areas calculated from angle-angle plots of pelvic and trunk rotations showed that coupling increased over game training (F(1,11) = 7.482, p = 0.019). Reaching to targets far from the midline required tighter coupling than reaching near targets (F(1,12) = 10.619, p = 0.007). CONCLUSIONS: Increasing coupling appears to be an initial compensation mechanism using the better controlled trunk to drive rotation of the pelvis. Co-contractions causing increased coupling are expected to reduce over longer exposure to training. The control scheme of the training game can be set to facilitate de-coupling of pelvic movements from the trunk. Using large ranges of pelvic rotation required more coupling suggesting that training of selective pelvic movements is likely to be more effective close to a neutral pelvic posture.